Penerapan Nilai-Nilai Pendidikan Agama Hindu Dalam Kitab Nitisastra Untuk Membentuk Perilaku Anak Suputra - Dian Tri Utami, Ni Nyoman; Wisnu Parta, Ida Bagus Made; Santiawan, I Nyoman; Yoga Pramana, Ida Bagus Kade; Sudiani, Ni Nyoman (Metta : Jurnal Ilmu Multidisiplin, 2023)
Hindu religious education is the implementation and internalization of values originating from the Vedic scriptures and other Hindu religious scriptures. One of the Hindu religious scripture that teaches about how to shape the behavior of superhuman children is the Nitisastra. The purpose of this study was to describe the application of Hindu religious educational values in the Nitisastra scripture to shape the behavior of the superhuman children. The method used is qualitative research, with data collection techniques namely observation, interviews and literature study. The results of the study show that Nitisastra contains knowledge about noble values and views of life in society that are worthy of being used as a way of life. In a family, naturally someone yearns for the birth of an ideal son according to the teachings of Hinduism, namely the son of suputra. A child who is virtuous, intelligent, wise, and proud of his family can be called a son of a son. The Nitisastra scripture can be used as a guide for parents to educate their children, because nowadays there are many cases of children who do not respect their parents. The Nitisastra scripture explains that the role of the family (father and mother) is to educate and shape the behavior of the sons of suputra so that one day they will be able to become the next generation.